(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2026)
Microplastics have become a global environmental concern in the 21st century due to their ubiquitous presence, particularly in the marine ecosystem. The current study investigates the occurrence, abundance, and distributional pattern of microplastics in the surface water of one of the most crucial fishing grounds in Bangladesh, the Middle Ground of the Bay of Bengal (BoB). The region is currently unexplored, despite the ongoing research on microplastics all over the world as well as in Bangladesh. Field sampling from 9 stations was conducted for water samples, and they were subsequently processed, digested, physically identified, and quantified. The mean abundance of microplastics was 2307 ± 2.9 microplastics/m3, while relative abundance of morphological shapes observed was as follows: pellets, fibers, foam, fragments, and film. However, transparent microplastics were the most dominant in terms of color. Smaller-sized particles (<0.5 mm) were predominant among the microplastic fractions. Based on risk assessments, the region falls under hazard category I, suggesting a minor risk. It was the first such investigation ever in the Middle Ground of the BoB, Bangladesh; therefore, the result of this study is expected to pioneer others and help mitigate policy implications for microplastic pollution in the BoB. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 14(2), 2025, P 163-176